Karakteristik Aus Mata Pisau Terlapisi Bahan Pengeras pada Pemotongan Kayu Mersawa dan Papan Partikel - Fauzan Fahrussiam; Wayan Darmawan; Imam Wahyudi; Hiroshi Usuki; Masahiro Yoshinobu; Shuhou Koseki (Jurnal Ilmu Pertanian Indonesia, 2017)
The use of mersawa wood and particleboard as a materials has been increasing for building constructions and decorative purpose. In previous study reported that, these materials provide a high rate of wear caused by abrasion (high silica) and resin content. This article presents the characteristics of wear on the clearance face of newly multilayer-coated K10 cutting tools when milling mersawa wood and particleboard. The K10 cutting tools were coated with monolayer titanium aluminum nitride (TiAlN), multilayer TiAlN/titanium silicon nitride (TiSiN), and TiAlN/titanium boron nitride (TiBN). Mersawa wood with density of 0.80 g/cm3 and particleboard with a density of 0.61 g/cm3 were cut using the coated tools and uncoated K10. Cutting tests were performed on computer numeric control router at a high cutting speed of 17 m/s and a feed rate of 0.1 mm/rev to investigate the wear characteristics on the clearance face of these coated tools. Result of research shown that the coated tools experienced a smaller amount of wear than the uncoated tool when cutting the mersawa and particleboard. The best coating among other coated in this study was multilayer TiAlN/TiBN. The high hardness, low coefficient of friction, high resistance to oxidation, and high resistance to delamination wear of the multilayer-coated TiAlN/TiBN tool indicate a very promising applicability of this coating for high-speed cutting of abrasive woods and wood based materials.